Efficacy and safety of tripterygium wilfordii multiglycosides in idiopathic membranous nephropathy: Protocol for an open-label randomized controlled clinical trial. Issue 6 (11th February 2022) - Geng, Chanyu; Li, Qiang; Pu, Lei; Yang, Hongling; Li, Guisen; Feng, Yunlin
Abstract: Objective: Tripterygium wilfordii multiglycosides has been demonstrated to be effective in reducing proteinuria and alleviate edema in patients with chronic kidney disease. We aim to evaluate its efficacy and safety in idiopathic membranous nephropathy. Methods and analysis: This is an randomized, open-labeled, controlled clinical trial. Twenty eligible patients with idiopathic membranous nephropathy will be randomly assigned into the intervention group and the control group at a rate of 1:1. Patients in the intervention group will receive tripterygium wilfordii multiglycosides tablets (1–1.5 mg/kg body weight/d, orally) in addition to the original treatment of angiotensin converting enzyme inhibitor/angiotensin receptor blocker, while the control group will continue with the original treatment of angiotensin converting enzyme inhibitor/angiotensin receptor blocker. The treatment course is 6 months, and clinical variables of patients will be measured at baseline and each monthly follow-up. The primary efficacy outcome measure is absolute decrease in urinary protein quantity after 6 months of treatment compared with baseline at randomization. The secondary efficacy outcome measures include absolute decrease in urine albumin-creatinine ratio in spot urine after 6 months of treatment compared with baseline at randomization, the percentage of patients who reached effective clinical response, and the percentage of patients who developed composite renal endpoint. Safety outcome measures include incidence of adverse events, incidence of serious adverse events, and death.